Knowledge and Attitude of Health Professionals toward Telemedicine in Resource-Limited Settings: A Cross-Sectional Study in North West Ethiopia. (18th November 2018) - Biruk, Kirubel; Abetu, Eden
Abstract : Background . In resource-limited environments, such as those categorized as underdeveloped countries, telemedicine becomes viewed as effective channel for utilizing the scarce medical resources and infrastructures. The aim of this study was to assess knowledge and attitude toward telemedicine among cross section of health professionals' working in three hospitals in North West Ethiopia. Methods . An institution-based cross-sectional study was conducted among 312 health professionals working in three different hospitals of North Gondar Administrative Zone during November 13 to December 10, 2017. Data were collected using structured self-administered questionnaires. Data entry and analysis were done using SPSS version 20. The mean, percentage, and standard deviation were calculated to describe the characteristics of respondents. The chi-square test was used as appropriate, to evaluate the statistical significance of the differences between the responses of the participants. AP value of < 0.05 was considered significant. Result . A total of 312 study subjects were approached and included in the study from November 13 to December 10, and the response rate was 95.5%. The majority of respondents (195 (65.4%)) were male, and the majority of the respondents (66.1%) were in the age group of 21–29 years. A large number of respondents (224 (75%)) were bachelor's degree holders. Only 37.6% of the respondents had demonstrated good knowledge of telemedicine, of which 74.1% were male, 65.2% of them were in the age group of 20–29 years, and 63.4% of them had >5 years of work experience. 191 (64.0%) respondents had good attitude toward telemedicine. Conclusion . The findings of the study suggest that although the respondents' knowledge of telemedicine is limited, most of them have good attitude toward telemedicine. This study underlined the need of giving training on telemedicine in order to fill the knowledge gap.